Fuzzy Mathematical programming approach for solving Fuzzy Linear Fractional Programming problem - Veeramani, C.; Sumathi, M. (2013 IEEE International Conference on Fuzzy Systems (FUZZ-IEEE), 2013)
In this paper, a method is proposed to solve Fuzzy Linear Fractional Programming (FLFP) problem where cost of the objective function, the resources and the technological coefficients are triangular fuzzy numbers. Here, the FLFP problem is transformed into an equivalent deterministic Multi-Objective Linear Fractional Programming (MOLFP) problem. By using Fuzzy Mathematical programming approach transformed MOLFP problem is reduced single objective Linear Programming (LP) problem. The proposed procedure illustrated through a numerical example.